Potency of PR controller for multiple harmonic compensation for a single-phase grid connected system - D Sattianadan; Soumen Gorai; G. R. Prudhvi Kumar; S. Vidyasagar; V. Shanmugasundaram (Institute of Advanced Engineering and Science, 2020)
Harmonics and grid synchronization are one of the major problems faced when dealing with a single-phase system. The development of technology in the PV system makes the consumer to use it in a wide range. The power transferred from PV to grid needs DC to AC conversion process which is done by static devices operating with the higher frequencies that causes the harmonics in the grid connected system. The main aim of the paper is to implement grid synchronization and reduce total harmonic distortion in a single-phase grid connected system. The design of LCL filter is addressed in this paper which depends on current ripple, filter size and switching ripple attenuation. In order to account the harmonic content, the FFT analysis is made both in analysis and Matlab Simulink. The Proportional Resonant (PR) controller is developed and work along with LCL filter for reducing the harmonic content. The stability of the system with PR is analyzed using root locus and bode plots and results are compared with PI controls. The result shows that PR controller performs better compared to the PI controller for reducing the harmonic content present in the single-phase system and for improving the system stability.